Improving the OCL Semantics Definition by Applying Dynamic Meta Modeling and Design Patterns - Chiaradia, Juan Martin; Pons, Claudia (Electronic Communications of the EASST, 2007)
OCL is a standard specification language, which will probably be supported by most software modeling tools in the near future. Hence, it is important for OCL to have a solid formal foundation, for its syntax and its semantic definition. Currently, OCL is being formalized by metamodels expressed in MOF, complemented by well formedness rules written in the own OCL. This recursive definition not only brings about formal problems, but also puts obstacles in language understanding. On the other hand, the OCL semantics metamodel presents quality weaknesses due to the fact that certain object-oriented design rules (patterns) were not obeyed in their construction. The aim of the proposal presented in this article is to improve the definition for the OCL semantics metamodel by applying GoF patterns and the dynamic metamodeling technique. Such proposal avoids circularity in OCL definition and increases its extensibility, legibility and accuracy.